2019
DOI: 10.1177/1040638719835243
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of Mycoplasma mycoides subspecies capri arthritis in young goats: a case study

Abstract: Brief Communication Mycoplasmas are commonly associated with pneumonic and arthritic lesions in goats. 5,15,16 Retrospective examination of University of Missouri Veterinary Medical Diagnostic Laboratory (VMDL) case records involving PCR 11 testing of mycoplasmosis in goats produced 77 records, exclusive of the cases described herein. Samples submitted from lung, joints, conjunctiva, genital secretions, milk, and blood were tested over a 13-y period (2005-2018). Of these, 45 (58%) yielded a positive result, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Since the early works, studies monitoring CA clinical features in endemic areas have been scarce 48. Prevalence studies are often conducted without taking into account whether there is or not some clinical aspects associated with isolation of mycoplasmas, see for instance,46,4952 while case reports are infrequent and often limited to narrow areas 43,5355. The main trend is that the classical overall picture of clinical CA has changed little, outside a few severe respiratory cases of Mmc infection in goats, initially suspected as contagious caprine pleuropneumonia 56–59…”
Section: Clinical Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the early works, studies monitoring CA clinical features in endemic areas have been scarce 48. Prevalence studies are often conducted without taking into account whether there is or not some clinical aspects associated with isolation of mycoplasmas, see for instance,46,4952 while case reports are infrequent and often limited to narrow areas 43,5355. The main trend is that the classical overall picture of clinical CA has changed little, outside a few severe respiratory cases of Mmc infection in goats, initially suspected as contagious caprine pleuropneumonia 56–59…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…General signs, such as weakness, pyrexia, or anorexia, that precede focal localizations often go unnoticed in adults whereas they can rapidly lead to mortality in young animals 48. Arthritis occurs frequently in young animals as a polyarthritis form causing recumbence, especially with Mcc 1,48 and Mmc ,54,55,64,68 but only occasionally in adults, where it causes lameness and swollen joints affecting mainly the tarsus and carpus 6963,69.…”
Section: Clinical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in an artificial insemination center in Spain revealed an increase in the incidence of Mmc latent infection in goats [16]. Recently, an outbreak of Mmc was reported in the United States of America [17] indicating the importance of this pathogen and the threats posed regardless of the available control methods.…”
Section: Introductionmentioning
confidence: 99%